2010
DOI: 10.1177/1066896910390680
|View full text |Cite
|
Sign up to set email alerts
|

Teratoma With Somatic-Type Malignant Components in Germ Cell Tumors of the Testis: A Clinicopathologic Analysis of 40 Cases With Outcome Correlation

Abstract: Teratoma with a malignant somatic component (MSC) is a rare phenomenon recognized when a somatic type malignancy occurs in the context of a germ cell tumor (GCT). The authors present their 29-year experience with 40 patients treated from 1981 to 2009 in their institution. The average age was 31 years. All patients underwent radical orchiectomy, which demonstrated a GCT in 19 with an MSC. The MSC was observed in the other 21 cases in metastatic sites, including lung (13), liver (3), pleura (1), mediastinum (7),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 26 publications
5
54
0
Order By: Relevance
“…Instead, grade of sarcoma, but not carcinoma, and diagnosis at late relapse were associated with cancer-specific mortality. Conversely, Colecchia et al [12 ]found stage at presentation to be a strong disease-related prognostic factor in their 40 cases. Lastly, a series of 33 cases by Guo et al [14 ]demonstrated that the presence of MST in metastasis is associated with higher rates of mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, grade of sarcoma, but not carcinoma, and diagnosis at late relapse were associated with cancer-specific mortality. Conversely, Colecchia et al [12 ]found stage at presentation to be a strong disease-related prognostic factor in their 40 cases. Lastly, a series of 33 cases by Guo et al [14 ]demonstrated that the presence of MST in metastasis is associated with higher rates of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to understand the prognostic factors and optimal management of this presentation of GCTs remain elusive as discussion is limited to case reports and a small number of published clinicopathologic series at referral centers [9,10,12,13,14,15,16]. To date, most studies have not shown significantly different survival outcomes between secondary somatic histologic subtypes [10,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It occurs in 3-6 % of patients with metastatic germ cell tumor (GCT). Further analyses have subsequently been reported, however, each one covering a small number of patients [5,7,10].…”
Section: Introduction and Historical Reviewmentioning
confidence: 96%
“…Clinical follow ups have shown that compared with teratomas without somatic type malignancies, these tumors in metastatic sites have poor prognosis if not completely resectable. The extent of the disease at onset and consequently, the feasibility of a radical surgical extirpation have been identified as the strongest prognostic parameters for durable remissions [3,[8][9][10].…”
Section: Introduction and Historical Reviewmentioning
confidence: 99%
See 1 more Smart Citation